The relationship between negative behaviors of students with intellectual disabilities in physical education and sports lessons and teachers’ burnout levels - Çoban, Bilal; Karakaya, Yunus Emre; Karademir, Tamer (Adam Marszalek Publishing House, 2016)
The purpose of this study was to reveal the relationship between the behaviors of students in physical education and sports lessons in Special Education Application Centers in Turkey and the burnout levels of physical education and sports teachers. The sample group of the study comprised 195 physical education and sports teachers who work in Special Education Application Centers. The data gathered from the study group were statistically analyzed using SPSS 18.0 for package software. In conclusion, the obtained findings demonstrated that the physical education and sports teachers in the study group were faced with the reality of burnout. © Wydawnictwo Adam Marsza?ek Toru? 2016.
Keywords: Burnout; Physical education and sports teachers; Student behaviors; Students with intellectual disabilities